Associations between MRI-detected early osteophytes and knee structure in older adults: a population-based cohort study. Issue 12 (December 2017) - Zhu, Z.; Laslett, L.L.; Han, W.; Antony, B.; Pan, F.; Cicuttini, F.; Jones, G.; Ding, C.
Summary: Objectives: To describe prevalence of osteophytes (OPs) detected only by magnetic resonance imaging (MRI) but not by standard X-ray in older adults and to evaluate longitudinal associations with knee structural changes. Methods: 837 participants were randomly selected from the local community and had MRI scans to assess knee OPs and other structures. OPs detected only by MRI but not by standard X-ray were defined as MRI-detected early OPs (MRI-OPs for short). OPs detected by both MRI and X-ray were defined as established-OPs. Results: The prevalence of MRI-OPs was 50% while the prevalence of established-OPs was 10% and no-OPs was 40% at total tibiofemoral (TF) compartment at baseline. Compared with no-OPs, participants with MRI-OPs had greater risks of increased cartilage defects in all TF compartments (RR 1.37, 95%CI 1.07–1.74) and bone marrow lesions (BMLs) only in medial TF compartment (RR 1.49, 95%CI 1.06–2.11), after adjustment for age, sex, BMI, cartilage defects, BMLs and/or joint space narrowing; participants with established-OPs had greater cartilage volume loss at total (β −2.02, 95%CI −3.86,  −0.17) and lateral tibial sites (β −5.63, 95%CI −9.93,  −1.32), greater risks of increased cartilage defects in total (RR 1.66, 95%CI 1.15–2.40) and medial TF compartments (RR 1.49, 95%CI 1.20–1.69) and BMLs in all TF compartments (RR 1.88, 95%CI 1.22–2.89), after adjustment for covariates. Conclusion: MRI-OPs were associated with changes in knee structures, and the associations were similar but not as prominent as those for established-OPs. These suggest MRI-OPs may have a role to play in knee early-stage osteoarthritic progression.